ALLELOPATHIC EFFECTS OF ROSE WOOD, GUAVA, EUCALYPTUS, SACRED FIG AND JAMAN LEAF LITTER ON GROWTH AND YIELD OF WHEAT ( Triticum aestivum L.) IN A WHEAT-BASED AGROFORESTRY SYSTEM - IQBAL,J. (2017)
ABSTRACT Selection of tree species under agroforestry systems is crucial to sustain the productivity of a crop. In present study, allelopathic effects of the leaf litters of 5 trees named Rose wood (Dalbergia sissoo), Guava (Pisidium guajava), Eucalyptus (Eucalyptus camaldulensis), Sacred fig (Ficus religiosa) and Jaman (Syzygium cumini) species on wheat growth and yield was examined. Leaf litter of each tress species was mixed in soil with two doses @ 100 and 200 g of leaves of each species per pot. Higher shoot length, shoot dry weight, number of spikelets per spike and biological yield were recorded in 200 g sun dried Jaman (Syzygium cumini) leaves. Total number of tillers per plant and number of ears per plant were higher under the application of Eucalyptus camaldulensis leaves (200 g sun dried) as compared to other treatments. Spike length, grain yield per pot, number of grains per pot and harvest index were maximum in 200 g sun-dried Sacred fig (Ficu sreligiosa) leaves. Majority of the parameters were promoted at lower doses of leaves per pot, however, at higher doses they started inhibiting the growth and grain yield of wheat.